2102-P: Upregulation of Adipose Tissue APOE Expression by ω3PUFA Supplementation Associates with Decreased Plasma FFA Levels and Improves Insulin Sensitivity in Obese Subjects - RAU, CASSANDRA; LI, TING; HERNANDEZ, JAMES D.; MASUDA, MIA Y.; ZHANG, XIAODONG; WANG, PANWEN; COLETTA, DAWN K.; DEFILIPPIS, ELEANNA (Diabetes (New York, N.Y.), 2019)
Inflammation of adipose tissue (AT) is key for the development of insulin resistance (IR) in obesity. We previously showed that 3 months supplementation of fish oil (FO, 4g/day), a well-known anti-inflammatory agent, induced 25% improvement in glucose disposal during euglycemic-hyperinsulinemic clamp in 13 obese, insulin resistant subjects (ADA abstract Hernandez J., et al 2017). To explore the mechanism(s) linked to this improvement, we first performed a microarray analysis of subcutaneous (SC) AT samples pre and post FO supplementation. Functional analysis indicated anti-inflammatory pathways as the principal pathways to be enriched after FO supplementation. We identified APOE (1.87 Fold Change (FC) Post vs. Pre-FO, P=0.004) among the most significantly enhanced genes, as APOE was common to the top 5 enriched anti-inflammatory pathways. RT-PCR analysis confirmed the changes in expression levels of several genes in these pathways including APOE, APOC1, MS4A6E, MMP9, MMP7, DEFB132, C1QTNF7, and POPDC3, thereby validating the microarray findings. Plasma and SC AT RT-PCR analysis showed significantly decreased inflammatory markers (IL1B: -0.28 FC, P=0.04, MCP1: -0.44 FC, P=0.04, CD68: -0.36 FC P=0.01) post vs. pre-FO. Additionally, mRNA adiponectin levels increased (FC +0.45 Post vs. Pre, P=0.02), while leptin decreased (FC -.030 Post vs. Pre, P=0.02). Furthermore, ω3PUFA supplementation significantly reduced plasma FFA levels (Post-FO: 0.578+0.061mM vs. Pre-FO: 0.719 +0.055mM P<0.05). Taken together, our data suggests that ω3PUFA supplementation-induced improvement of insulin sensitivity in obese, insulin resistant subjects is attributed to the reduction of plasma FFA levels. This then associates with inhibition of inflammatory processes mediated by APOE. Additional studies are needed to further analyze the mechanism(s) linking FO to AT APOE gene expression, inflammation and insulin sensitivity.